Assessment of the Effects Exerted by Acid and Alkaline Solutions on Bone: Is Chemistry the Answer?. Issue 5 (1st February 2017) - Amadasi, Alberto; Camici, Arianna; Porta, Davide; Cucca, Lucia; Merli, Daniele; Milanese, Chiara; Profumo, Antonella; Rassifi, Nabila; Cattaneo, Cristina
Abstract: The treatment of corpses with extremely acid or basic liquids is sometimes performed in criminal contexts. A thorough characterization by chemical analysis may provide further help to macroscopic and microscopic analysis; 63 porcine bone samples were treated with solutions at different pH (1–14) for immersion periods up to 70 days, as well as in extremely acidic sulfuric acid solutions (9 M/18 M) and extremely basic sodium hydroxide. Inductively coupled optical emission spectrometry (ICP‐OES)/plasma mass spectrometry (ICP‐MS), Fourier transform infrared spectroscopy (FT‐IR), energy dispersive X‐ray analysis (EDX), X‐ray powder diffraction (XRPD), and scanning electron microscopy (SEM) showed that only the sulfuric acid solution 18 M was able to completely dissolve the sample. In addition, chemical analysis allowed to recognize the contact between bone and substances. Hydrated calcium sulfate arose from extreme pH. The possibility of detecting the presence of human material within the residual solution was demonstrated, especially with FT‐IR, ICP‐OES, and EDX.